Does Central Bank Quality Determine Sovereign Ratings and Credit Default Swap Spreads: Evidence from the World? - Indranarain Ramlall (Journal of Central Banking Theory and Practice, 2016)
This study innovates from prior research which focuses on the determinants of sovereign ratings and credit default swap spreads for a large sample of countries by incorporating the quality of central banks, let alone refined proxies. Findings show that the explanatory power of both sovereign ratings and CDS spreads model improve by a hefty 11 percent in case of sovereign ratings and 6 to 9 percent in the case of CDS spreads when central bank quality is incorporated. Such a finding bolters the notion that institutional quality does play a preponderant role when it comes to assessing country risk, making it a systematic component of institutional quality. The effect of labour participation implies that countries buffeted by stronger effects of an ageing population have greater propensity of increases in CDS spreads. Evidence is also found as to the driving dynamics of CDS spreads and sovereign ratings to be distinct. Our results hold robust post tackling for endogeneity problem.
Keywords: E02; E58; F30; G00; 330; Central Banking; Credit Default Swap Spreads; Sovereign ratings; Country risk analysis.